Linking metal–organic cages pairwise as a design approach for assembling multivariate crystalline materials. Issue 1 (6th December 2021) - Markwell-Heys, Adrian W.; Roemelt, Michael; Slattery, Ashley D.; Linder-Patton, Oliver M.; Bloch, Witold M.
Abstract : A new strategy to design atomically precise multivariate metal–organic frameworks is presented. This is achieved by linking two preformed metal–organic cages via a precisely tuned Rh–aniline interaction. Abstract : Using metal–organic cages (MOCs) as preformed supermolecular building-blocks (SBBs) is a powerful strategy to design functional metal–organic frameworks (MOFs) with control over the pore architecture and connectivity. However, introducing chemical complexity into the network via this route is limited as most methodologies focus on only one type of MOC as the building-block. Herein we present the pairwise linking of MOCs as a design approach to introduce defined chemical complexity into porous materials. Our methodology exploits preferential Rh-aniline coordination and stoichiometric control to rationally link Cu4 L4 and Rh4 L4 MOCs into chemically complex, yet extremely well-defined crystalline solids. This strategy is expected to open up significant new possibilities to design bespoke multi-functional materials with atomistic control over the location and ordering of chemical functionalities.